Effects of production systems and ozone treatment on nitrate content and E. coli O157:H7 contaminations of Butterhead lettuce - Yusoff, Siti Fairuz (2013)
Butterhead lettuce, a salad crop pose to food safety risk issues because it is normally consume raw. The information regarding nitrate and Escherichia coli O157:H7 contaminations status on Butterhead lettuce in Malaysia is still scanty. Not much work of this nature is carried out locally. Recently, an outbreak of E. coli was happened in Germany, which one of the most stringent countries in term of food safety on fresh produce. Hence, this study seemed inevitable to be carried out. The first experiment, a market study, to determine the level of nitrate and E. coli O157:H7 contaminations of Butterhead lettuce. The result showed that nitrate levels exceeded the maximum limit but the bacteria contaminations were still under safe limit. The second experiment was to determine the effect of harvesting stage on the nitrate content, quality and nitrate reductase activity (NRA) of Butterhead lettuce, grown by hydroponic and organic systems. After 35, 38, 41 and 44 days of transplanting (DAT),the lettuce harvested and the studied effects were determined. Nitrate content in hydroponic lettuce was higher compared to organic lettuce. The accumulation varies with leaf parts, the highest being in midribs, followed by outer adult leaf blades and young leaves. For hydroponic lettuce, extended harvesting stage was found to reduce nitrate content. Fourty one DAT was the optimum stage to harvest with significantly higher reduction of nitrate content. At this stage, the fresh weight, firmness and color were still acceptable. However, harvesting stage had no effect on nitrate content in organic lettuce. NRA was found to be higher in young leaves compared with outer adult leaf blades and midribs. The third experiment was to determine effect of different aqueous ozone concentrations on E. coli O157:H7, nitrate and nitrite contents, and postharvest quality of Butterhead lettuce. The lettuce was treated with aqueous ozone at concentrations of 0, 3 and 5 mg.Lˉ¹ and stored at 10 °C for 12 days. The quality was assessed on day 0, 4, 8 and 12 of storage by comparing the changes. The number of E. coli in organic lettuce was found to be higher than hydroponic lettuce. The aqueous ozone at 5 mg.Lˉ¹ treatments was effective in reducing E. coli colonies but with quality compromised and the effectiveness decreased as the storage period progressed. Ozone at 3 mg.Lˉ¹ was a potential concentration on reducing E. coli without giving in to quality. In conclusion, the consumers and producers should apply hygienic practices to ensure safe consumption. The optimum harvest stage of Butterhead lettuce is at 41 DAT. A potential concentration of aqueous ozone was 3 mg.L-1 on reducing E. coli O157:H7 contamination without detrimental effects on lettuce quality. Lettuce can be stored in cool storage for up to eight days.